2008
DOI: 10.1111/j.1939-1676.2008.00216.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Isoflurane General Anesthesia or Anesthesia and Surgery on Thyroid Function Tests in Dogs

Abstract: Background: Anesthesia and surgery affect thyroid function tests in humans but have not been studied in dogs. Hypothesis: Anesthesia and anesthesia with surgery will affect thyroid function tests in dogs. Animals: Fifteen euthyroid dogs. Methods: Prospective, controlled, interventional study. Dogs were assigned to one of 3 groups: control, general anesthesia, and general anesthesia plus abdominal exploratory surgery. Dogs in the anesthesia and surgery groups were premedicated with acepromazine and morphine, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(7 reference statements)
1
3
0
Order By: Relevance
“…An increase in serum rT3 has been reported during NTI in humans [ 27 ]. A similar increase has been reported in healthy euthyroid dogs during general anesthesia and surgery [ 28 ], and in a small population of healthy dogs following endotoxin administration [ 18 ]; however, no similar results in canine species during spontaneous SIRS have been reported. In the present study, the median concentration of rT3 was not significantly different between SIRS and control dogs.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…An increase in serum rT3 has been reported during NTI in humans [ 27 ]. A similar increase has been reported in healthy euthyroid dogs during general anesthesia and surgery [ 28 ], and in a small population of healthy dogs following endotoxin administration [ 18 ]; however, no similar results in canine species during spontaneous SIRS have been reported. In the present study, the median concentration of rT3 was not significantly different between SIRS and control dogs.…”
Section: Discussionsupporting
confidence: 77%
“…Derangement of the thyroid axis was documented in chronic inflammatory conditions and during heterogeneous non-thyroidal diseases [ 13 15 23 ]. Finally, significant abnormalities in thyroid function test results have been reported in healthy euthyroid dogs during anesthesia or surgical procedures [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two studies in dogs have demonstrated that anesthesia and surgery alter serum TT4, TT3, and fT4 concentrations, but any significant change from baseline occurred within 8 to 12 hours after implementation of these interventions. 52 , 53 To minimize the impact of anesthesia and surgery on thyroid function tests, dogs had initial blood sampling performed before these interventions and subsequent blood samples were obtained a minimum of 12 hours afterward. Moreover, when serum thyroid hormone concentrations were compared between the dogs managed medically and those undergoing anesthesia and surgery, no significant differences were found except for the serum TT3 concentration at 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Cats used in the study were acclimated to blood collection and were sampled only once daily, randomly over 6 days, eliminating the need for an IV catheter or anesthesia for blood collection. This design helped to minimize any potential effect of additional drugs or procedures on thyroid hormone concentrations; surgery and anesthesia have been shown to suppress thyroid hormone concentrations in dogs and humans 15 and similar effects are also likely in cats.…”
Section: Discussionmentioning
confidence: 99%